(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
We are part of the information society. New technologies are being formed as atool of social construction. In this frenetic progress, not all people have access equally. Either by material resources and / or personal limitations groups is left out of this process, which is shaping the society’s technology. From the General Direction of Social Services (Family and Social Affairs Department) Region of Madrid, introduce general experiences and specific RAIS`s experience “El Rincon del Encuentro” (“Meeting point corner”) (low demand for the homeless people) and discussed have been implemented as access to new technologies (Internet) in the operation of the centre from the methodology of the social inclusion towards people affected by acutesituations of social exclusion. (General Direction of Social Services, Family andSocial Affairs Department, Region of Madrid).